Effectiveness of Probiotic Yogurt and Homemade Curd on Salivary pH, Buffering Capacity, and Salivary Calcium Level in 12-year-old School Children in Nellore City: A Randomized Controlled Trial - Vaishnavi Kondepudi; R. V. S. Krishna Kumar; Gomasani Srinivasulu; Punamalli Symon Prasanth (Wolters Kluwer Medknow Publications, 2024)
Introduction Numerous noninvasive strategies are used to prevent dental caries. Remineralization can take place by the use of milk and milk products. Another approach to bacterially mediated diseases has been the use of probiotics. The classic food containing probiotic is yogurt (curd) and consumption of dairy products on daily basis seems to be most natural and effective way to ingest probiotic bacteria. Aim The aim of this study is to evaluate the effect of probiotic homemade curd and yogurt on salivary pH, calcium level, and buffering capacity. Materials and Methods A total of 52 students aged 12 years, who met the inclusion criteria were randomly selected from two different schools and were divided into two groups. Test and control group consumed 200 mL of probiotic yogurt and curd for a period of 30 days. Baseline and 30 days of unstimulated salivary sample (2 ml) was collected and salivary pH, buffering capacity and salivary calcium level was assessed. The data were statistically analyzed. Results The mean salivary pH and buffering capacity was found to be same in both groups and salivary calcium levels increased with the use of probiotic yogurt at the end of 30 days compared to control group. Conclusion The consumption of probiotic yogurt for a short period of time can prevent dental caries by increasing salivary calcium levels.